PENINGKATAN AKTIVITAS SOSIAL SISWA DALAM PEMBELAJARAN BIOLOGI MELALUI PENERAPAN MODEL PEMBELAJARAN STAD DISERTAI VIDEO DI KELAS VII SMP NEGERI 1 JATEN - Achrudin, Achrudin; Sajidan, Sajidan; Indrowati, Meti (P Biologi FKIP UNS Surakarta, 2013)
ABSTRACT ? The objective of the research is to improve social activities of students in biology learning through implementing STAD learning model with video assisted. This study was a classroom action research which was carried out in two cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. Subjects were students of class VII-F SMP Negeri 1 Jaten Karanganyar in the academic year 2011/2012. Data was obtained through observation, questionnaires, and interviews. Then, data was analyzed by using descriptive analysis technique and was validated by using triangulation technique. The results showed that the implementation of STAD learning model with video assisted could enhance social activities of students in biology learning. The increase average value of student?s social activities achievements based on observation after the first cycle was 6.61%, then it reached 4.91% for the second cycle. However, the final achievement gained 67.26%. Based on these results, it could be concluded that implementing STAD learning model with video assisted could enhance social activities of students in biology learning class of VII-F in SMP Negeri 1 Jaten Keywords: cooperative learning, STAD, video assisted, student?s social activities